2017
DOI: 10.1016/j.lcsi.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic literacy: Talking, reading and writing among primary school children

Abstract: This study investigates the interplay between talk, reading and writing as Mexican primary school children worked together, in small groups, on a psycholinguistic task that required them to read three related texts and write an integrative summary. The study was conducted in the context of an educational program called 'Learning Together' (LT), which uses collaborative learning to enhance the development of children's oracy and literacy. Analyses of children's dialogues using the Ethnography of Communication i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
0
20
0
4
Order By: Relevance
“…Ada banyak penelitian yang mengeksplorasi praktik literasi di kalangan anak-anak usia sekolah di daerah pedesaan dan / atau masyarakat sosial ekonomi rendah, namun sebagian besar dari mereka berpusat pada masalah seputar lingkungan sekolah (lihat, misalnya, (Andersen et al, 2018;Chen, Rea, Shaw, & Bottino, 2016;Frey, Lee, Tollefson, Pass, & Massengill, 2005;Rojas-Drummond et al, 2017). Pada kenyataanya, ada waktu-waktu di luar jamsekolah yang dapat dimanfaatkan untuk mempropagandakan gerakan literasi tersebut.…”
Section: Pendahuluanunclassified
“…Ada banyak penelitian yang mengeksplorasi praktik literasi di kalangan anak-anak usia sekolah di daerah pedesaan dan / atau masyarakat sosial ekonomi rendah, namun sebagian besar dari mereka berpusat pada masalah seputar lingkungan sekolah (lihat, misalnya, (Andersen et al, 2018;Chen, Rea, Shaw, & Bottino, 2016;Frey, Lee, Tollefson, Pass, & Massengill, 2005;Rojas-Drummond et al, 2017). Pada kenyataanya, ada waktu-waktu di luar jamsekolah yang dapat dimanfaatkan untuk mempropagandakan gerakan literasi tersebut.…”
Section: Pendahuluanunclassified
“…The previous research states that to improve students' mathematical communication abilities, a learning model is needed. One learning model that can improve mathematical communication is Think Talk Write (TTW) learning model, (Elida, 2012;Hendriana, 2014;Kurniaman, 2018;Nuraeni, 2018;Rahman, 2012;Suminar, 2018;Winayawati, 2012;Rojas-Drummond, 2016). The TTW learning model is a cooperative learning model that was first introduced by Huinker and Laughin in 1996.…”
mentioning
confidence: 99%
“…Sociocultural environments thus influence the choice of writing strategies, since writing expertise grows through the internalization of generally accepted strategies and procedures for addressing writing problems, which are shared within a community of practice (Deane et al, 2018). Rojas-Drummond, et al (2017) employ the term dialogic literacy, which refers to the interplay between talk, reading and writing. The authors found that 6th-graders' ability to co-construct knowledge and produce a coherent synthesised summary, was highly dependent on their ability to talk and think together.…”
Section: To Collaborative Writing As Literacy Practicesmentioning
confidence: 99%
“…Second, on the basis of the Vygotskian view of learning as a basically social activity. Rojas-Drummond, et al (2008) have demonstrated how writing together can evoke different processes of collective creativity, brainstorming and intersubjectivity, and Rojas-Drummond, et al (2017) found that 6th-graders' ability to co-construct knowledge and produce a coherent synthesised summary, was highly dependent on their ability to talk and think together. According to Rivard and Straw (2000), talk is important for sharing, clarifying and distributing knowledge, and writing may help the development of more structured and coherent ideas, as the writers move to higher-order and more complex cognitive processes (Chen, 2011).…”
Section: Collaborative Writing and Content Learningmentioning
confidence: 99%